2012
DOI: 10.1136/bcr-2012-007397
|View full text |Cite
|
Sign up to set email alerts
|

Cirrhosis, cellulitis and cats: a ‘purrfect’ combination for life-threatening spontaneous bacterial peritonitis fromPasteurella multocida

Abstract: SummaryPasteurella multocida is a Gram-negative coccobacillus that colonises the upper airways of many animals, in particular, dogs and cats. It acts as an opportunistic infection in humans following an animal bite or scratch and is associated with soft tissue infections, septicaemia and pneumonia, particularly in patients with a compromised immune response, such as patients with liver failure. Spontaneous bacterial peritonitis (SBP) is a serious complication of cirrhosis with a death rate of 10-15%. We report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…One bacterium (monomicrobial) is the cause in more than 90% of cases, yet the probability of identifying a pathogen is mediocre as ascitic fluid cultures are positive in 50–60% of patients with SBP . Rare isolates reported in the literature include anaerobes, Aeromonas , Listeria , Streptococcus bovis , Bordetella bronchiseptica , Candida , Pasteurella multocida , Leclercia adecarboxylata , and Salmonella paratyphi A…”
Section: Bacteriologymentioning
confidence: 99%
“…One bacterium (monomicrobial) is the cause in more than 90% of cases, yet the probability of identifying a pathogen is mediocre as ascitic fluid cultures are positive in 50–60% of patients with SBP . Rare isolates reported in the literature include anaerobes, Aeromonas , Listeria , Streptococcus bovis , Bordetella bronchiseptica , Candida , Pasteurella multocida , Leclercia adecarboxylata , and Salmonella paratyphi A…”
Section: Bacteriologymentioning
confidence: 99%
“…Among the Pasteurella species, P. multocida is the predominant human pathogen encountered, especially in severe disease cases (235,239), although P. canis may be more prevalent with dog bites (48, [246][247][248]. Common symptoms of pasteurellosis in humans from animal bite wounds are swelling (edema), cellulitis (diffuse, localized inflammation with redness and pain), and bloody or suppurative/ purulent exudate (drainage) at the wound site (39, 41, 48, 49, 160,165,241,[249][250][251][252][253][254][255]. Leukocyte and neutrophil counts are typically high at the infection site, and inflammation develops very rapidly.…”
Section: Pasteurella and Other Pasteurellaceae Diseases In Humans Pasmentioning
confidence: 99%
“…16,17 Elderly patients with diabetes mellitus, hypertension, acquired immunodeficiency syndrome, malignancies and cirrhosis are the most vulnerable towards the development of such infections. Hey et al 18 reported a case of a 47-year-old man with cirrhosis who developed a life-threatening spontaneous peritonitis and bacteremia due to Pasteurella multocida following the lick from a cat on a cellulitic wound.…”
mentioning
confidence: 99%